PENERAPAN PETA KONSEP UNTUK MENINGKATKAN KEMAMPUAN SISWA MENULIS REPORT TEXT - Atik Zulaikah (LPMP Provinsi DKI Jakarta, 2022)
The ability writing is the important aspect to be increased for senior high school student. The experiment purposes to improve writing of report text outcome through mind mapping for students of Class X IPS. The participants who were 34 students were chosen by purposive sampling technique. The instrument consists of test and non-test. Test instrument consists of 1 item and it is essay. Non test instrument is an observation sheet. Giving written test and observation sheets were carried out as data collecting techniques. The data collecting procedure were analyzed based on the cycles, the classroom action research as an experiment method. An increase in the learning outcomes, namely cycle I completeness by 67,94 showed as the result. The completeness became 72,35 in cycle II and the completeness became 78,82 in cycle III. The assessment of students’ skill has increased in the first cycle of completeness to 20,59%. Cycle II completeness 44,11% and cycle III the completeness 76,47%. With the target achieving 75% completeness, it means that the improvement of learning due to Mind mapping. Based on this research, mind mapping can improve writing capability in report text.